EFFECT ON LIFE STYLE FOR HYPERTENSION(STUDY IN JABON VILLAGE, JOMBANG SUBDISTRICT, JOMBANG REGENCY) - Gita Mayangsari; Evi Rosita; Dwi Prasetyaningati (Jurnal Keperawatan, 2013)
Hypertension cause unhealthy lifestyle,actually lifestyle factors important effect for society. Unhealthy lifestyle can make hypertension, purpose examination to know lifestyle for hypertension in jabon village jombang subdistrict regency jombang. Detail examination survey analytic with cross sectional. Population all victims of hypertension in jabon village jombang subdistrict jombang regency are 108 people take with simple random sampling until get 32 people. Variable independent in this examination lifestyle and variable dependent are in case of hypertension. Get data with spread questionnaire and observations use stethoscope and tense. After collecting did processor data and continue tests statistics chi square with level significantly 0,05 use spss 16 for Windows.Result examination can get by test che squares with spss,on level error 5% and value p 0.006, in p = 0,0006<0,05. Summary in this examination that truly lifestyle on hypertension in jebon village jombang subdistrict jombang regency. healthyworkers can make learning to society about lifestyle to hypertension victims so that hypertension victims understand how to decrease effect with programs hospital.